Bounds of sixth-order Toeplitz determinant for the families of function associated with bounded turnings - Erzig, Omar S.; Juma, Abdul Rahman S.; Al-Fayadh, Ali (Iraqi Journal of Science, 2025)
This research focused on studying the Toeplitz determinants for classes of functions with bounded turnings. Before that, some previous studies of Hankel's determinants have been discussed, due to their strong association with Toplitz determinants. They share most of the mathematical features. For example, if the transpose of both matrices is taken, then the original matrix is obtained. On the other hand, for the set BT of univalent functions with bounded turnings, estimates of the sixth-order Toeplitz determinants have been provided in the unit disc. Besides, the sixth Toeplitz determinant for the  and  was found, which subfamilies of the  family.